Ethanol promotes apoptosis in rat ovarian granulosa cells via the Bcl-2 family dependent intrinsic apoptotic pathway - Liu, Yu; Zuo, Haojiang; Wang, Yao; Tian, Liantian; Xu, Xin; Xiong, Jingyuan; Pei, Xiaofang (Cellular and Molecular Biology, 2018)
Excessive and indulgent alcohol consumption causes tremendous public health issues worldwide. Not only is ethanol associated with a broad spectrum of critical chronic diseases, ethanol is also demonstrated to exert striking reproductive toxicity for both males and females. Epidemiological investigations suggested that ethanol is closely related to fertility decrease in women. Animal studies showed that ethanol intake obstructed ovulation and reduced ovarian weight during gestation. However, cellular mechanism for this inhibitory effect of ethanol on female fertility is yet to be explored. This study recruited rat ovarian granulosa cells, the primary effector of ovary, to investigate the effects of ethanol on cell apoptosis and explore potential mechanism. Ovarian granulosa cells treated with ethanol for three hours manifested observable reduction in cell viability and apparent apoptosis. In the presence of 200 and 300 mmol/l of ethanol, the percentages of apoptotic cells increased to 33% and 36%, respectively. In addition, apoptosis related caspase-3 activity was elevated with increasing concentrations of ethanol, suggesting a dose dependent effect. Furthermore, high concentrations of ethanol significantly disturbed the transcriptional and translational regulation of anti-apoptotic Bcl-2 and pro-apoptotic Bax, which are the two key members of Bcl-2 family tightly involved in intrinsic apoptotic pathway. These results indicated that ethanol promotes apoptosis in rat ovarian granulosa cells, possibly via the intrinsic apoptotic pathway.